2016
DOI: 10.3389/fpls.2016.00756
|View full text |Cite
|
Sign up to set email alerts
|

Is Wortmannin-Induced Reorganization of the trans-Golgi Network the Key to Explain Charasome Formation?

Abstract: Wortmannin, a fungal metabolite and an inhibitor of phosphatidylinositol-3 (PI3) and phosphatidylinositol-4 (PI4) kinases, is widely used for the investigation and dissection of vacuolar trafficking routes and for the identification of proteins located at multivesicular bodies (MVBs). In this study, we applied wortmannin on internodal cells of the characean green alga Chara australis. Wortmannin was used at concentrations of 25 and 50 μM which, unlike in other cells, arrested neither constitutive, nor wounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 81 publications
(146 reference statements)
1
24
0
Order By: Relevance
“…Recent evidence suggests that, in a green alga, formation of these vesicles may be reduced by treatment with the phosphatidylinositol kinase inhibitor, wortmannin [63]. We note, however, that application of wortmannin to C/ w Str1 cells can be complicated by its short half-life in culture media (8–13 minutes), and off-target effects such as induction of nitric oxide production and protein phosphorylation (http://www.enzolifesciences.com/BML-ST415/wortmannin/).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that, in a green alga, formation of these vesicles may be reduced by treatment with the phosphatidylinositol kinase inhibitor, wortmannin [63]. We note, however, that application of wortmannin to C/ w Str1 cells can be complicated by its short half-life in culture media (8–13 minutes), and off-target effects such as induction of nitric oxide production and protein phosphorylation (http://www.enzolifesciences.com/BML-ST415/wortmannin/).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the light-induced pH bands in Chara cells disappear after the treatment with an inhibitor of phosphoinositide 3-kinases (PI-3 kinase), wortmannin, 13 indicating the involvement of phosphorylated phosphoinositides in the generation of pH bands. Phosphoinositides have an important regulatory role in cell physiology.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of tubular structures reminiscent of charasomes after the inhibition of lipid phosphorylation by wortmannin indirectly suggests the rearrangement of lipid material trafficking and possible disturbance of the charasome-mediated proton extrusion. 13 Since the pH banding pattern in resting cells is coordinated with the patterns of photosynthetic activity and charasome frequency, the influence of wortmannin on photosynthetic activity is likely.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ERL1-YFP predominantly resides on the MVB. This is further confirmed by a pharmacological approach using Wortmannin (Wm), a fungal drug that can cause fusion of MVBs by inhibiting phosphatidylinositol-3 (PI3) and phosphatidylinositol-4 (PI4) kinases (Foissner et al, 2016). The Wm application on Arabidopsis seedlings resulted in the formation of typical ring-like Wm bodies marked by both ERL1-YFP and RFP-Ara7 (Figure 1C).…”
Section: Resultsmentioning
confidence: 84%